Case Report: A 13-year-old adolescent diagnosed as malignant phyllodes tumor combined with rhabdomyosarcoma differentiation - Lian, Jie; Gao, Lu; Yao, Ru; Zhou, Yidong; Sun, Qiang (Frontiers in Oncology, 2023)
Phyllodes tumor (PT) is an infrequent type of breast neoplasm, constituting a mere 0.5%-1.5% of the entirety of breast tumors. The malignant phyllodes tumor (MPT) comprises only 15% of all phyllodes tumors, and its transformation into rhabdomyosarcoma (RMS) is exceedingly rare in clinical practice. Given its insensitivity to chemotherapy and radiotherapy, treatment options for MPT patients MPT are limited, leaving complete surgical resection as the only option. Therefore, it is imperative to investigate the effective utilization of the heterogeneous differentiation characteristics of MPT to expand treatment alternatives for these patients. In this case report, we represent a 13-year-old adolescent diagnosed as giant breast MPT with RMS differentiation and pulmonary metastasis. The initial step in the treatment process involved radical surgical resection, followed by the administration of 4 cycles of VDC/IC chemotherapy, which is widely recognized as the standard chemotherapy for RMS. Regrettably, the delay in initiating chemotherapy resulted in minimal observable changes in the size of the pulmonary metastatic nodule. Additionally, a comprehensive literature review on the characterization of MPT with heterogeneous differentiation was conducted to enhance comprehension of the diagnosis and treatment of this uncommon disease in clinical practice. Meanwhile, this case also reminds the doctors that when we diagnose a patient as MPT, it is crucial to consider its heterogenous nature and promptly initiate adjuvant treatment. By targeting the differentiation element of MPT, it becomes feasible to overcome the previously perceived limitation of surgical intervention as the sole treatment option.